The reality of the role of the Presidency of the Grand Mosque and the Prophet’s Mosque in managing the crisis under the COVID-19 pandemic is a model - Al-Zahrani, Tariq Khames (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to learn about the role of the General Presidency of the Holy Mosque and the Prophet’s Mosque in managing the crisis in the light of the COVID-19 pandemic. The study sample consisted of 274 researchers from workers and dealers with the Grand Mosque and the Prophet’s Mosque. The study tools were a questionnaire to collect data and information from the study’s sample. The results of the study reached a high level of role played by the Presidency of the Grand Mosque and the Prophet’s Mosque in managing the crisis under the COVID-19 pandemic from the point of view of the study sample, where the overall average value of 4.566 was a standard deviation of 0.721 "The level of success of the General Presidency of the Holy Mosque and the Prophet’s Mosque in the face of the spread of the coronavirus has risen from the point of view of the study sample, with the overall average of 4.607 with a standard deviation of 0.692. The results also showed that one of the most important ways to overcome the challenges of interacting with visitors and destinations of the holy mosque and the Prophet’s mosque was to apply all precautionary measures, followed by providing several sites to presidential officials, focusing on the enrichment and media application on electronic social media, the development of guidance and awareness boards, the imposition of penalties for violators, and the continuous sterilization of congregations. The study recommended that action should be taken to maintain the outstanding level provided by the Presidency of the Holy Mosque and the Prophet’s Mosque in the face of crises through the use of modern means of early detection and the need to develop the management of the risks of infectious diseases in gatherings.